2009
DOI: 10.1358/mf.2009.31.3.1362512
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of tianeptine pretreatment in rats exposed to acute stress and repeated severe stress

Abstract: In this study we aim to discuss the relationship between stress and learning and emotionality in an experimental model using two different stress conditions: acute stress (single restraint stress for 20 min) and repeated severe stress (6-h daily restraint for 21 days). We studied the effects of tianeptine, which has been suggested to have anxiolytic and cognition-enhancing effects under stressful conditions. After acute stress, the increase in the duration of immobility (F = 5.753 and 3.664) in the open field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Our results also did not appear to be confounded either by motivational or motor factors as indicated by no significant different in the distance travelled and swim speed during the acquisition phase between the control and stressed groups. Our results during the probe trial supported previous studies which showed that no significant difference was observed between control and stressed groups, which indicates that chronic stress did not affect spatial memory [14, 16, 36]. However, our results contradicted studies that showed chronic stress either impaired [1, 18, 20] or facilitated spatial memory [11] in the water maze test.…”
Section: Discussionsupporting
confidence: 85%
“…Our results also did not appear to be confounded either by motivational or motor factors as indicated by no significant different in the distance travelled and swim speed during the acquisition phase between the control and stressed groups. Our results during the probe trial supported previous studies which showed that no significant difference was observed between control and stressed groups, which indicates that chronic stress did not affect spatial memory [14, 16, 36]. However, our results contradicted studies that showed chronic stress either impaired [1, 18, 20] or facilitated spatial memory [11] in the water maze test.…”
Section: Discussionsupporting
confidence: 85%
“…The available data suggest that acute restraint stress induces mixed effects in hippocampus-dependent learning and memory tasks, with most labs showing significant impairments in tasks such as the Morris water maze (Kasar et al, 2009 ; Buechel et al, 2014 ) and others showing significant improvements (Zheng et al, 2007 ). Performance in cognitive tasks that are thought to depend on the extended hippocampal network, such as novel object recognition (Aggleton and Brown, 2005 ; Barker and Warburton, 2011 ) are also negatively affected by acute stress (Guercio et al, 2014 ; Vargas-Lopez et al, 2015 ).…”
Section: Arc In Mdd-related Animal Modelsmentioning
confidence: 99%
“…Additionally, female rodents subjected to 6 h restraint stress per day for 21 days performed significantly better in the same radial arm maze task (Bowman et al, 2009 ). However, in the Morris water maze and Barnes maze, chronic stress universally seems to impair performance (Kasar et al, 2009 ; Bian et al, 2012 ; Tian et al, 2013 ; Rinwa and Kumar, 2014 ; Huang et al, 2015 ; Trofimiuk and Braszko, 2015 ). Thus, although there are some complexities in terms of how chronic stress modulates performance in hippocampus-dependent cognitive tests, on average stress seems to impair performance, at least in male subjects.…”
Section: Arc In Mdd-related Animal Modelsmentioning
confidence: 99%